Kajian Saluran Drainase di Sekitar Kecamatam Penguguran Menjadi Kolam Ikan Air Bergerak Untuk Penambahan Pendapatan Masyarakat Sekitar - Novdin M. Sianturi; H Asril Nizar; Ricardo Simamora (Insight Power (Kekuatan Wawasan), 2022)
Villages around the Porsea District, Toba Samosir Regency, need to be rearranged either by way of counseling to the community related to the meaning of the environment as seen from the scientific point of view of civil engineering where the landslide disaster occurred suddenly without the community around the village. around the area realize that when the rainy season comes where it is necessary to hold socialization of the rearrangement of the drainage channel, it can be used as a moving water fish pond drainage channel according to the regulations of the local environmental service. Porsea Subdistrict, Toba Samosir Regency, which has a large area of land / settlements that require drainage channel planning so that it can be used as a fish pond drainage channel in increasing the income of local residents which is beneficial for the community in the village around the Porsea Subdistrict, T Regency. oba Samosir and can overcome the problem of overflowing water when it rains suddenly with maximum rainfall in the area with a lot of data that must be prepared in advance in order to evaluate the drainage channel which can function as a fish pond with running water in the village in around the Porsea District, Toba Samosir Regency, if the program runs well. In community activities in making fish pond drainage channels in the Village around the Porsea District, Toba Samosir Regency, work partners are indispensable in carrying out every activity where the role of the Village Head around the Region is indispensable in implementing the program in order to increase the income level of local residents. To implement government programs in advancing and increasing the income of residents in villages around the Porsea District, Toba Samosir Regency, a new breakthrough is needed by utilizing unproductive drainage channels into productive drainage channels by cultivating freshwater fish along the planned 195 meter long drainage channel where conditions The drainage channel is still in shape, namely with a channel top width of 100 cm, channel height 100 cm and a channel bottom width of 80 cm and around the Village in the Porsea District, Toba Samosir District, and the need to build sluice gates every 50 meters so that the water level in the drainage channel remains stable. and the arrangement of the floodgates when raising the water level must be controlled every day so that during the rainy season there are no floods. Keywords: Drainage, Fish Ponds, Utilization of Waterways, Community Income